FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI KERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH PETALA BUMI PROVINSI RIAU TAHUN 2017 - Ahmad Satria Efendi, Tiara, Sandi Iljanto, (Menara Ilmu, 2019)
It was found in matters that could be used to work from a salary replacement systemprovided with a reward system for exemplary nurses to be disbursed by hospitals thatcould cause low-level nurses to work in public hospitals on this earth. Therefore, this studyaims to determine the factors associated with the work motivation of nurses in the inpatientward. PetalaBumi Regional General Hospital of Riau Province 2017, Training andcommunication and communication. This research is analytic observational analytic (crosssectional). The number of samples in this study was 43 nurses. Data analysis techniqueswere univariate and bivariate using chi square test, followed by multivariate testing usingmultiple logistic regression. From the results of bivariate analysis, 79.1% of nurses withlow motivation. From the results of the analysis of multivariate variables, the largestvariable for work in the inpatient room is Communication (OR: 22,569 95% CI 1,724-295,510 and education and training variables and variables as confounding variables forphysical variables. Functional to improve personal relationships between nurses,harmoniously intertwined, and can also be done by returning the reward system for nursenurses and lingering and motivated to become exemplary nurses.Key Words : Nurse Motivation, Compensation, Safety and Health Insurance,Training, Communication